I will Always Follow You: Exploring the Role of Customer Relationship in Social Media Marketing - Laksamana, Patria (International Review of Management and Marketing, 2020)
This article aims to examine the mediating role of customer relationship in social media marketing. Its affect on purchase intention and brand loyalty is also analyzed. The conceptual model was tested in the context of retail banking. Data were collected by self-administered survey with 286 respondents. The results provide evidence that social media marketing leads to customer relationship, purchase intention and brand loyalty. However , the affect of social media marketing on purchase intention and brand loyalty were stronger when it was mediated by customer relationship. From a theoretical standpoint the results of this study contribute to further understanding the importance of customer relationship in social media marketing. Whereas for managerial perspective, it determines the social media marketing strategy for improving purchase intention and brand loyalty. Keywords: Customer relationhip, social media marketing, purchase intention and brand loyalty. JEL Classification: M31 DOI: https://doi.org/10.32479/irmm.9662